Pendidikan Kesehatan dengan Media Audiovisual Mempengaruhi Perilaku Pasien TB Paru dalam Pencegahan Infeksi Nosokomial COVID-19 di Puskesmas - I Ketut Suardana; Komang Trisna Handayani; I Made Mertha; I Wayan Surasta (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2021)
Patients with tuberculosis with weak immune systems susceptible to develop nosocomial infections, so that promotive and preventive efforts are needed while the patient is in control of treatment. The aims of this study is to determine the effect of health education with audiovisual media to prevention of COVID-19 nosocomial infection behavior at Patient with pulmonary tuberculosis at Community Health Center Seririt I. This research was conducted in April 2021. The type of this research is Pre- Experimental designs with One-Group Pretest-Posttest design. The sample was selected using purposive sampling technique with 11 respondents. The results showed that the average value of pulmonary tuberculosis patient behavior before being given audiovisual health education, is 57,15 in the sufficient category and after education with audiovisual media 85,34 in the good category. The paired T-test results ρ - value = 0.001 α (0.05), that mean health education with audiovisual media is effective for changing behavior of pulmonary tuberculosis patients in the prevention of COVID-19 nosocomial infection. Health service providers such as puskesmas can increase health promotion efforts, especially for pulmonary TB patients so that they are not exposed to nosocomial infections.